Study of Electronic Structure of Boron-Nitride /Graphene Bilayer by Using DFT - A. Algharagholy, Laith; M. Abduljalil, Hayder; A. Marhoon, Haidar (Al-Qadisiyah Journal of Pure Science, 2018)
In this work, we study the electronic structure (number of open channels (NOC), band structur(BS), density of states (DOS), and I-V curve) of boron nitride/ graphene sheet using SIESTA and GOLLUM codes. Ab initio structural optimization performs for all structures using the local density approximation (LDA) with norm-conserving pseudopotentials, double zeta polarized (DZP) basis sets of pseudoatomic orbitals, and the Ceperley-Alder exchange correlation functional with the atomic forces relaxed to 0.02 eV/˚A. Three types of simulated heterostructures sheets have been studied: 1- One graphene strip and one boron nitride strip sheet. 2- Two graphene strip and one boron nitride strip sheet. 3- Three graphene strip and one boron nitride strip sheet. We show that there is a dramatic reduction in energy gap ‘Eg’ of heterostructures comparing with the insulator boron nitride (Eg4.6 eV) and increasing in energy gap comparing with semimetallic graphene (zero gap).